Anatomical considerations for thread-based brow lifting and wrinkle treatment - Hong, Gi-Woong; Wan, Jovian; Yoon, Song-Eun; Wong, Sky; Yi, Kyu-Ho (The Journal of dermatological treatment, 2025)
This review explores the anatomical considerations and technical aspects of thread lifting for the forehead and eyebrow, focusing on the relationships between vascular structures, muscular anatomy, and age-related changes in the forehead-eyebrow complex. It highlights the critical importance of understanding neurovascular pathways, particularly the supratrochlear and supraorbital vessels, as well as the appropriate thread placement techniques necessary for optimal outcomes. The review demonstrates that I-shaped threads, when placed beneath the frontalis muscle, provide a safer and equally effective alternative to traditional U-shaped designs. Additionally, the review emphasizes the significance of preoperative assessment, especially the evaluation of tissue mobility and adhesion patterns, in predicting procedural success. The review concludes that combining thread lifting with volumising monofilaments offers a comprehensive approach to rejuvenating the forehead-glabellar region, while minimizing the risk of complications. This study's clinical impact lies in its potential to enhance both the safety and efficacy of thread lifting procedures, offering practitioners a refined technique for esthetic rejuvenation of the forehead and eyebrow complex.